Conditioning of the territory in Peru - De la Cruz Lapa, Primo (2000)
Peru presents a scenario where the socio-economic activities are carried out, as very different levels of reliefs Plain in the coastal desert, the Andes, the subtropical Mountain (Ceja de Selva) and Amazonia. Each of these vertical divisions has very special ecological, economic and social characteristics. The system determines the Peruvian Current ichthyological richness of the sea and along the Cordillera evens climate along the coast. Just as the lack of rain and its desert nature. The valleys of the coastal rivers rises steeply from sea level to 4 000 to 5 000 meters. altitude, rarely surpassing 100 km. Thereby giving rise to a possibility of physical connection of the Coast with the Sierra, which has been used to construct the main access roads to the mountain and forest.